PENGARUH PENGGUNAAN WINDOW DISPLAY TERHADAP GAMBARAN URETER DENGAN KASUS UROLITHIASIS PADA PEMERIKSAAN CT STONOGRAM DI RSUP DR.HASAN SADIKIN BANDUNG : THE EFFECTS OF WINDOW DISPLAY USAGE ON THE URETER IMAGES WITH UROLITHIASIS RESULTED BY CT STONOGRAM EXAMINATION IN CENTRAL GENERAL HOSPITAL OF DR. HASAN SADIKIN BANDUNG - Rahmat, Lili Julia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2022)
MSCT stonogram plays an important role in establishing diagnosis in urolithiasis. The examination technique is carried out without the use of contrast agents as required in other modalities. The purpose of this study was to determine the effect of window level on MSCT stonography on ureteral images. The research was conducted at RSUP.DR.Hasan Sadikin Bandung. This is an analytic observational research with a cross-sectional study design. Tools used in this research are MSCT Hitachi scenaria 128 slices, multi planar reformat (MPR) and curve planar reformat (CPR) image reconstruction using Terarecon with iNtuition client software ver 4.4.12.100. Data were taken from 14 random samples of patients with urolithiasis cases who had undergone MSCT stonography examination. The data were assessed by three Consultant Radiologists and then analysed by a statistical test of IBM SPSS statistics ver. 25.0 in 2019. Results showed that Ho was rejected and Ha was accepted. They explain that the change in the window level on the MSCT stonogram examination with urolithiasis cases affects the resulted ureteral images with p value of 0.041 (p < 0.05). Therefore, it can be concluded that the use of window width 350 and Window level 60 can visualize very clear pictures of the ureter after CPR reconstruction.